Explorating Digital Skills Readiness: The Role of Digital Literacy, Access to Digital Tools Resources, and Self-Efficacy - Maharani, Raissa Susilo; Sari, Nadilah Sintia (Lentera Ilmu Nusantara, 2025)
This study discusses the influence of Digital Literacy Training and Access to Digital Tools and Resources on Digital Skills Readiness in the context of manufacturing companies in Bekasi Regency, by considering the mediating role of Self-Efficacy In Digital Tasks in digital tasks. In the ever-evolving digital era, digital skills readiness is a crucial issue for industry, especially in facing the industrial revolution 4.0. This study aims to explore the relationship between these two factors and digital skills readiness, which include technical, information, and collaboration skills. The method used is quantitative research with a sample of respondents working in the manufacturing sector. The results of the analysis show that Digital Literacy Training has a significant positive impact on Digital Skills Readiness, while Access to Digital Tools and Resources also contributes to improving employees' digital skills. However, the role of Self-Efficacy In Digital Tasks as a mediator shows insignificant results in this relationship. These findings emphasize the importance of investing in Digital Literacy Training to improve the digital skills of the workforce. From a practical perspective, this study provides clear guidance for HR managers and policymakers to prioritize structured training programs and equitable access to digital tools, while not overly relying on self-efficacy assumptions, in order to strengthen workforce preparedness. This study is expected to provide insight for companies and policy makers in designing effective digital skills development strategies, so that they can support innovation and competitiveness of the manufacturing industry in Indonesia.